The Dilemma of Social Media Benefits to College Programming Students - Mvurya , Mgala; Mwakondo, Fullgence (Multidisciplinary Journal of Technical University of Mombasa, 2023)
Social media has become part and parcel of students’ life in colleges as it occupies most of their free times. Over time, results of programming units have shown a downward trend among college students at Technical University of Mombasa in Kenya. Programming, like Mathematics, requires a lot of practice that is now consumed by social media. This study investigated the impact of Social Media on Grades in terms of hours spent and the time of day Social Media is used. Descriptive statistical research was used to gain understanding of the predictive power Social Media has on the Programming Grades. A total of 142 students pursuing Degree and Diploma courses in Information Technology participated in the study. The students were drawn from Technical University of Mombasa and Kenya Coast National Polytechnic. Over 90% of the students were active Social Media users. The research was conducted in 2018-2019 academic year. Results show that social media use could predict students who scored high grades in both Degree and Diploma courses. Such students controlled their usage of Social Media. They did not use Social Media in the early morning hours up to afternoons when they were engaged in serious studies. These students used Social Media anytime of the day - which means, in between serious study sessions. On the other hand, more average students used Social Media even in the early morning and up to afternoon sessions. Notably, more average Diploma students use Social Media at bedtime than anytime. Further research is recommended with more data using Machine Learning techniques to develop a model that will predict success or failure in Programming units depending on how one uses social media.